Music As A Social Emotional Therapy Media For Mentally Retarded Children At Yayasan Pembinaan Anak Cacat (YPAC) Semarang (Jurnal Seni Musik, 2022)
The purpose of this study was to identify and describe the music used as social-emotional therapy for mentally retarded children at YPAC Semarang and its application. This research uses a qualitative approach.Technique of data collection through observation, interview and documentation. The validity of the data was checked by triangulation, data sources, adequacy of references, and extension of participation. Data analysis was carried out using an interactive data analysis model which was taken through the process of data reduction, data presentation, and drawing conclusions/verification. The results showed that the music used as a medium for emotional social therapy was divided into two, namely music whose sound source came from the body and music whose sound source came from musical instruments. Both are divided into pitchless music and pitched music. The application of music as a medium of emotional social therapy is carried out through several stages, namely, In the first therapeutic process, students are not directly given material about music. The next stage of therapy refers to the psychomotor domain, and the next stage, after the students are considered capable, teacher begins to teach simple musical instruments to students.